Apoptotic and antiproliferative effects of Stigmast-5-en-3-ol from Dendronephthya gigantea on human leukemia HL-60 and human breast cancer MCF-7 cells. (October 2018) - Fernando, I.P. Shanura; Sanjeewa, K.K. Asanka; Ann, Yong-Seok; Ko, Chang-ik; Lee, Seung-Hong; Lee, Won Woo; Jeon, You-Jin
Abstract: The genus Dendronephthya encompasses marine soft corals that produce a wide spectrum of biofunctional terpenoids. Anticancer properties of these metabolites are widely exploited as potential chemotherapeutic agents. The present study reports the purification and isolation of a potential antiproliferative constituent, stigmast-5-en-3-ol from the 70% ethanol extract of the soft coral Dendronephthya gigantea . Among several other 3β-hydroxy-Δ5-steroidal congeners, stigmast-5-en-3-ol indicated prominent antiproliferative effects on HL-60 (leukemia) and MCF-7 (breast cancer) cell lines with IC50 values of 37.82 and 45.17 μg/ml respectively. Stigmast-5-en-3-ol increased apoptotic body formation, accumulation of sub G1 apoptotic cells, and DNA damage in HL-60 and MCF-7 cells. It increased the expression of Bax, caspases, and PARP cleavage while decreasing Bcl-xL levels in both cancer cell lines indicating that the effects are arbitrated via the mitochondria-mediated apoptotic pathway. Steroidal derivatives were identified by GC MS/MS and the identity of stigmast-5-en-3-ol was confirmed by NMR spectra. The present study suggests that stigmast-5-en-3-ol could be a promising candidate for anticancer drug research. Graphical abstract: Highlights: Stigmast-5-en-3-ol was isolated from a sterol rich fraction of Dendronephthya gigantea . Stigmast-5-en-3-ol decreased HL-60 and MCF-7 cancer cell proliferation. Stigmast-5-en-3-ol induced apoptosis via mitochondria-mediated pathway.